Comparison between three methods of diode laser 810 nm, photodynamic therapy with laser 660 nm, and hypochlorite solution for disinfection of pulp canal of primary teeth - Nima Amini Tehrani; Shahrzad Javadinejad; Amir Mansour Shirani (Wolters Kluwer Medknow Publications, 2024)
Background: The presence of treatment-resistant microorganisms is known as the main cause of pulpectomy failure in the endodontic treatment of deciduous teeth. The usage of lasers can contribute to reducing these microorganisms. This study aimed to compare the effect of three disinfection methods for deciduous teeth canals using laser diode 810 nm, photodynamic therapy with laser 660 nm and methylene blue, and sodium hypochlorite. Materials and Methods: In this experimental study, 58 single-root deciduous teeth with no root resorption were investigated in four groups, including one control group of 10 and three intervention groups of 16. Preparation of the samples was done using manual files up to three numbers after the initial file. After sterilizing the samples in an autoclave, Enterococcus faecalis bacteria were cultured in the canals. In the first group, irrigating with hypochlorite 2.5% was done; in the second group, photodynamic therapy was performed using a laser diode and 0.1 mg/mL methylene solution; and in the third group, high-intensity laser 810 nm direct radiation was done into the canal. Next, samples were taken from all canals. The colony formation unit (CFU) of the bacteria was counted in the blood agar culture medium. The data were analyzed using Kruskal-Wallis and negative binomial regression test (α =0.05). Results: The mean CFU differed significantly between the four groups. The rate of incidence of E. faecalis colonies showed a reduction in all three intervention groups compared to the negative control. In the high-intensity laser 810 nm group, there was 68.4%; in the photodynamic therapy with diode 660 nm and methylene blue, there was 88%; and in the hypochlorite group, 98.3% reduction was observed compared to the negative control group. Conclusion: Based on the results of this study, to compare three disinfection methods of the deciduous teeth canals without preparation of canals, sodium hypochlorite had greater efficiency. All three groups of laser, photodynamic therapy, and sodium hypochlorite showed reductions of E. faecalis bacterial colony compared to the control group. The reductive effects of CFU were greater in the hypochlorite sodium group, followed by photodynamic and direct laser radiation groups.